The role of community density in the development of elite handball and football players in Denmark - Rossing, N.; Nielsen, A.; Elbe, A.; Karbing, D. S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Birthplace studies (Macdonald et al., 2009; Cote et al., 2006) highlight the critical role that an individual`s early environment plays in facilitating athletic development and participation in sport. These studies have shown across various sports and nations that elite athletes tend to come from communities with 100.000-500.000 inhabitants (Cote et al. 2006). Bruner et al. (2011) suggested that the proportional number of youth players could explain the effect, which later studies have supported. The purpose of this study was to investigate which communities, Danish elite football and handball players primarily have lived during their development years and which communities have the highest proportions of youth players. Method: The sample included 366 male handball and football players from the best Danish leagues in the season 2011-2012 and a comparison sample of 147,221 football and 26,290 handball male youth players under the age of 12 from 2003 corresponding to the youth development years of the elite players. Communities were divided into six subdivisions by population density. Population density was used as a proxy since this should reflect the built and the psychosocial environment. Odds ratios (OR) were calculated for community sub-divisions by comparison with census statistics. Results were considered significant if 95% confidence intervals (CI) for OR did not include 1. Results: Communities with the highest density (.1000 pop./square km) produced a disproportionately high number of elite football players (OR [CI]) (2.08 [1.55-2.81]). Contrary to football, communities with a medium population density (100 to < 250 pop. /km2) produced a higher number of elite handball players (1.79 [1.27-2.53]). However, there were few youth players in both sports in communities with high density (. 1000 pop. / square km) (football: (0.70 [0.69-0.71]), handball: (0.48 [0.46-0.50]), and an overrepresentation in rural communities (< 50 pop. /km2) (football: (1.42 [1.40-1.44]), handball: (1.81 [1.81-1.81]). Discussion: The study indicates that communities with different population densities affect the talent development process, and that it is sports dependent. This may be due to built and psychosocial environment, such as sport facilities, sports culture etc. Youth and elite players were overrepresented in different density sub-divisions indicating that the birthplace effect is not only related to the number of registered youth players in Danish football or handball.